2014
DOI: 10.3109/13880209.2014.919326
|View full text |Cite
|
Sign up to set email alerts
|

Chemical profile and biological activities ofVeronica thymoidessubsp.pseudocinerea

Abstract: The methanol extract having strong antioxidant and DNA damage effects could be investigated phytochemically to find natural active compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
1
23
1
1
Order By: Relevance
“…According to scanning electron microscope (SEM) investigation, non-glandular trichomes (Figure 2a,b,g,h) were unbranched, bi-cellular to multicellular, uniseriate, and folded at different levels. They could be noted as attenuate trichomes [17]. The length of these trichomes varied from very short to long trichomes (Figure 2g,h).…”
Section: Micromorphological Traitsmentioning
confidence: 94%
See 1 more Smart Citation
“…According to scanning electron microscope (SEM) investigation, non-glandular trichomes (Figure 2a,b,g,h) were unbranched, bi-cellular to multicellular, uniseriate, and folded at different levels. They could be noted as attenuate trichomes [17]. The length of these trichomes varied from very short to long trichomes (Figure 2g,h).…”
Section: Micromorphological Traitsmentioning
confidence: 94%
“…Palmitic acid was also found in the EO of the species Veronica thymoides P. H. Davis subsp. pseudocinerea M. A. Fischer, where it accounted for 5.4% of the total EO [17].…”
Section: Gas Chromatography and Mass Spectrometry (Gc-ms) Analysis Ofmentioning
confidence: 99%
“…Mocan et al [12] found in veronica orchidea, officinallis, teucrium, antioxidants, phytochemical and antimicrobial. Dunkic et al [13] in veronica spicataconfirmed antioxidants plus antimicrobial while Exarchou [14] isolated compounds hispidulin also antiviral [15] an effective anti-cancer, anti-mutagenic and antitumor with new compounds [16][17][18][19] anti-ulcerogenic [20,21] anti-cholinesterase [22] antiinflammatory [18] anti-insecticidal [23] anti-hepatocarcinoma [24] antioxidants [25] angiogenic, neuroprotective potency [26] wound healing, cough, catarrh, and kidney medication [12] natural preservatives, dietary supplement, and hyperglycemia [27,28] was reported in this genus species, Javadsharif rad et al [29] found in veronica persicapoiracetylcholinesterase, scolicidal, tyrosinase, xanthine oxidase, lipoxygenase. Our current study is to focused only on antioxidant analysis by (1,1-diphenyl-2-picryl-hydrazyl) method and phytochemical confirmation also yield calculation for the first time in the genus veronica medicinal plant a specie veronica biloba.…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil were diluted using CH 2 Cl 2 (1:3 v/v) prior to GC/FID and GC/ MS analysis. The GC/MS and GC/FID procedure described by Ertas et al [15] were applied. GC/FID performed using Thermo Electron Trace GC FID detector and GC/MS performed using same GC and Thermo Electron DSQ quadrupole for MS.…”
Section: Extraction Of Essential Oil and Gc/ms Conditions Steam Distimentioning
confidence: 99%
“…Consequently, consumers have been more interested in natural antioxidants to protect their health [14]. Additionaly, recent several scientific studies have been focused on the phenolic compounds of the plants having a number of pharmacological effects and the biological activities [15].…”
Section: Introductionmentioning
confidence: 99%